SOCIAL HEALTH AND DEMENTIA: INDIVIDUAL, INTERDISCIPLINARY AND INTERNATIONAL PERSPECTIVES. (11th November 2018) - Kolanowski, A M; Roes, M; Downs, M
Abstract: The definition of health should include a more dynamic focus on the ability of individuals to adapt and self-manage physical, mental and social well-being despite the presence of chronic conditions. In 2016 the European InterDem's Social Health Taskforce operationalized three dimensions of Social Health for dementia: (1) having the capacity to fulfil one's potential and obligations; (2) the ability to manage life with some degree of independence; and (3) participation in social activities. In this symposium we bring together presenters, both scientists and people living with dementia, who will share their personal experiences and data on the concept of Social Health in dementia. We begin with a brief overview of the concept from the European perspective. The first presentation is given by members of a stakeholder group of persons living with dementia who informed the U.S. 2017 National Research Summit on Dementia Care; they will expand on the moral imperative of facilitating the capacity to fulfil one's potential. The second presenter will report on findings from the NIA-funded COPE project that teaches family caregivers how to help their relatives with dementia manage life with greater independence by adapting the home environment to facilitate maximum function and safety. The final presenter will share data on the transferability and effectiveness of the Meeting Centres Support Programme, an intervention that promotes the social activity of persons with dementia and their families across Europe. The discussant will bring together these diverse individual, interdisciplinary and international perspectives on Social Health.